Etymological features of the verbs of speaking - Timoshilova, Tamara M.; Morozova, Elena N.; Zimovets, Natalya V.; Kolesnikov, Aleksei A.; Serkina, Olesya V. (Universidade Estadual Paulista, 2021)
The article deals with the etymological analysis of the verbs expressing thoughts (express, flourish, phrase, term, utter, vent, verbalize, vocalize, voice, word) in the perspective of semantics. The changes in the life of society are reflected in the semantic and word-forming structure of verbal formation. Verbs expressing thoughts could be no better able to describe the state of modern society, which in the last decades of the XXI century, the century of communication and information, is impossible to imagine without such concepts as interaction, communication, giving and receiving information, expressing ideas and thoughts. The verb is not enough to consider as a symbol of different processes, actions and states. It has the ability to “convert” the information about time, space, the idea of the subject, the object of the action and its tool. The activation of the situation occurs due to the metonymic and metaphorical transformations that underlie the nomination of the whole situation by the verb.